Common Ribs of Inhibitory Synaptic Dysfunction in the Umbrella of Neurodevelopmental Disorders - Ali Rodriguez, Rachel; Joya, Christina; Hines, Rochelle M. (Frontiers in Molecular Neuroscience, 2018)
The term neurodevelopmental disorder (NDD) is an umbrella term used to group together a heterogeneous class of disorders characterized by disruption in cognition, emotion, and behavior, early in the developmental timescale. These disorders are heterogeneous, yet they share common behavioral symptomatology as well as overlapping genetic contributors, including proteins involved in the formation, specialization, and function of synaptic connections. Advances may arise from bridging the current knowledge on synapse related factors indicated from both human studies in NDD populations, and in animal models. Mounting evidence has shown a link to inhibitory synapse formation, specialization, and function among Autism, Angelman, Rett and Dravet syndromes. Inhibitory signaling is diverse, with numerous subtypes of inhibitory interneurons, phasic and tonic modes of inhibition, and the molecular and subcellular diversity of GABAA receptors. We discuss common ribs of inhibitory synapse dysfunction in the umbrella of NDD, highlighting alterations in the developmental switch to inhibitory GABA, dysregulation of neuronal activity patterns by parvalbumin-positive interneurons, and impaired tonic inhibition. Increasing our basic understanding of inhibitory synapses, and their role in NDDs is likely to produce significant therapeutic advances in behavioral symptom alleviation for interrelated NDDs.